Evaluation of Diabetes Mellitus bearer towards basic health care attention in Rio Grande do Norte - Santos-Neto, Alcebíades José dos; Pereira, Álison Wílian de Souza; Medeiros, Clístenes Stênio Lima de; Macêdo, Marcos Antônio Costa Ferreira de; Costa, Nilma Dias Leão; Costa, José Vílton (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2016)
Background/purpose: The Diabetes Mellitus (DM) is considered one of the main causes of death for non-communicable chronic diseases (NCCD) in the world, stating a considerable prevalence in Brazil as well. Therefore, the purpose of this study is to analyze the satisfaction of the DM patients taken care at public primary health system in the state of Rio Grande do Norte (RN), and also, to present the situation about the services offered to these patients. Methods: This is a descriptive study, using data from “External Evaluation Instrument of Access Improvement and Quality of Primary Care Program” (known as PMAQ-AB), regarding the state of RN, as held from May to August of 2012, with a total of 119 attendees. Results: In accordance with the patients, the primary health care unity (PHCU) works on days and shifts correctly (84%) and such timeframe comply with their needs (82%), with an average of waiting time on about 31 minutes and rendering sufficient time with the doctor (89%), although insuch appointment the patients don’t have their feet examined (82,4%) or receive proper advice about feet care (63%). Only five users (4,2%) needed to pay for medication and almost 80% have considered the health care provided as good or very good. Conclusion: The study evidenced the access to the PHCU and to medication, the reception, the physical infra-structure and satisfaction of the patients with the care provided as well evaluated. Although certain improvement is needed regarding the continuity of the treatment and thoroughly physical examination as carried out.